Myanmar's Education Reforms A pathway to social justice? - Lall, Marie (UCL Press, 2021)
This book reviews the state of education in Myanmar over the past decade and a half as the country is undergoing profound albeit incomplete transformation. Set within the context of Myanmar's peace process and the wider reforms since 2012, Marie Lall's analysis of education policy and practice serves as a case study on how the reform programme has evolved. Drawing on over 15 years of field research carried out across Myanmar, the book offers a cohesive inquiry into government and non-government education sectors, the reform process, and how the transition has played out across schools, universities and wider society. It casts scrutiny on changes in basic education, the alternative monastic education, higher education and teacher education, and engages with issues of ethnic education and the debate on the role of language and the local curriculum as part of the peace process. In so doing, it gives voice to those most affected by the changing landscape of Myanmar's education and wider reform process: the students and parents of all ethnic backgrounds, teachers, teacher trainees and university staff that are rarely heard. Marie Lall argues that, despite a commitment to greater equality and equity expressed in the Ministry of Education's policy documents, Myanmar has missed a historic opportunity to make use of education reform to engage with deep-seated social injustices. Inequalities persist in the long-term outcomes for poorer sections of society and between the majority Bamars and ethnic nationality communities. This is the portrait of a country constrained by internal tensions and competing international priorities that serve to divert the professed course towards social justice.